ARA-C, IDARUBICINE AND GENTUZUMAB OZOGAMICIN (AIM) AS SALVAGE TREATMENT IN ADVANCED ACUTE MYELOID LEUKEMIA PATIENTS - saveria capria; silvia maria trisolini; clara minotti; caterina stefanizzi; luisa cardarelli; Martina Canichella; claudio cartoni; daniela diverio; maria stefania de propris; marco mancini; alessandra micozzi; robin foà; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Long-term survival of relapsed/refractory acute myeloid leukemia (AML) remains a major problem, particularly in patients not eligible for transplantation.